Flux creep in pulsed laser deposited superconducting YBa₂Cu₃O₇ thin films - Maritz, E. J. (Erasmus Jacobus) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Physics))--University of Stellenbosch, 2002.